Deficiency of the Novel Exopolyphosphatase Rv1026/PPX2 Leads to Metabolic Downshift and Altered Cell Wall Permeability in Mycobacterium tuberculosis - Chuang, Yu-Min (mBio, 2015)
Mycobacterium tuberculosis can persist for decades in the human host. Stringent response pathways involving inorganic polyphosphate [poly(P)], which is synthesized and hydrolyzed by polyphosphate kinase (PPK) and exopolyphosphatase (PPX), respectively, are believed to play a key regulatory role in bacterial persistence. We show here that M. tuberculosis poly(P) accumulation is temporally linked to bacillary growth restriction. We also identify M. tuberculosis Rv1026 as a novel exopolyphosphatase with hydrolytic activity against long-chain poly(P). Using a tetracycline-inducible expression system to knock down expression of Rv1026 (ppx2), we found that M. tuberculosis poly(P) accumulation leads to slowed growth and reduced susceptibility to isoniazid, increased resistance to heat and acid pH, and enhanced intracellular survival during macrophage infection. By transmission electron microscopy, the ppx2 knockdown strain exhibited increased cell wall thickness, which was associated with reduced cell wall permeability to hydrophilic drugs rather than induction of drug efflux pumps or altered biofilm formation relative to the empty vector control. Transcriptomic and metabolomic analysis revealed a metabolic downshift of the ppx2 knockdown characterized by reduced transcription and translation and a downshift of glycerol-3-phosphate levels. In summary, poly(P) plays an important role in M. tuberculosis growth restriction and metabolic downshift and contributes to antibiotic tolerance through altered cell wall permeability.